Oriental Institute Notes. Note 9: A “Syro-Hittite” Treasure in the Oriental Institute Museum - Kantor, H.
The Disk — Pendants in the Form of a Bull’s Head — Cylinder Seal and Gold Pin — Gold Armlets — Gold Sheatings and Silver Vessels — Metal Analyses — Conclusion.